Bioconversion of meat and bone meal and starch into astaxanthin - Li, Sang (Kansas State University, 2019)
Astaxanthin is a valuable superior antioxidant and has been extensively used in cosmetics, pharmaceuticals, food applications, and animal feed. In present studies, valorization of rendering by-products (meat and bone meal-MBM) and corn/wheat starches into astaxanthin through biotransformation with Paffia rhodozyma was investigated. First, the effect of carbon (glucose) to nitrogen (yeast extract+peptone) (C/N) ratio in the P. rhodozyma fermentation media on astaxanthin production was studied, and the optimal C/N ratio of 5 was achieved to obtain maximum astaxanthin content of 3.6 mg/g dry cell biomass. Secondly, MBM was utilized as a nitrogen source for astaxanthin production. MBM was hydrolyzed by enzymes (proteinase) and alkaline (i.e., carbon hydroxide] to convert protein into soluble amino acids to supply nitrogen source for P. rhodozyma fermentation. With 40 g/L glucose and alkaline MBM hydroysate, P. rhodozyma fermentation achieved a maximal astaxanthin content of 1.02 mg/g dry cell biomass. At last, corn and wheat starches were studied as carbon sources for astaxanthin production by P. rhodozyma. Starches were hydrolyzed by amylase and glucoamylase into glucose, starches hydrolysates were diluted by distilled water for further fermented by P. rhodozyma for astaxanthin production. The corn and wheat starches achieved maximum astaxanthin contents of 2.15 mg/g dry cell biomass and 3.62 mg/g dry cell biomass, respectively. Future work is needed to further enhance the astaxanthin yield to produce astaxanthin yield of industrial interest.
Keywords: Astaxanthin; Phaffia rhodozyma; Meat and bone meal; Starch; Hydrolysis; Fermentation